Prospective study of mycobacterial infections in patients with cystic fibrosis. Issue 5 (May 1990) - Hjelte, L; Petrini, B; Källenius, G; Strandvik, B
Abstract : Fifty four patients with cystic fibrosis, aged 3-67 years, were studied prospectively for pulmonary mycobacterial infection. Sputum smears and cultures were carried out and intradermal skin tests performed. Mycobacteria were cultured from six patients in association with clinical deterioration; four patients had positive direct smears. Mycobacterium tuberculosis, M aviumintracellulare, M kansasii, and M gordonae were isolated. There were no deaths and all improved with chemotherapy. A third of the other 48 patients had positive skin test responses (greater than 6 mm) to purified protein derivative (PPD) tuberculin and 21 to one or more antigens prepared from non-tuberculous mycobacteria. Sensitisation increased with age; before the age of 11 only one patient had a positive response to PPD tuberculin and none to any other antigen. This was less than in healthy control subjects of similar age. After age 11 the reactions in sensitised patients were stronger than in positive healthy control subjects. Our study indicates that it is important to consider mycobacterial infection in patients with cystic fibrosis who deteriorate without obvious cause.